1995
DOI: 10.1007/bf01980487
|View full text |Cite
|
Sign up to set email alerts
|

Munchausen syndrome by proxy and factitious illness: Symptomatology, parent-child interaction, and psychopathology of the parents

Abstract: The term Munchausen syndrome by proxy is used to diagnose children presenting symptoms of an organic disorder resulting from manipulations initiated by their caretakers. Even in early infancy it happens that injuries are induced, and that drugs, poisons or medicine are administered in order to provoke and feign clinical symptoms of severe diseases. Exact data on prevalence are not available but it is obvious that Munchausen syndrome by proxy is a rare psychiatric disorder. There is a body of evidence that Munc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Comparado com outras doenças pediátricas, a DFI é rara, com incidência aproximada de 0,5/100 000 crianças menores de 16 anos, prevalência variando de 0,02% a 1,8% das crianças 11,12 e mortalidade estimada em 9% 13 . Certamente esses dados são subnotificados, pois é uma condição altamente complexa de ser diagnosticada.…”
Section: Discussionunclassified
“…Comparado com outras doenças pediátricas, a DFI é rara, com incidência aproximada de 0,5/100 000 crianças menores de 16 anos, prevalência variando de 0,02% a 1,8% das crianças 11,12 e mortalidade estimada em 9% 13 . Certamente esses dados são subnotificados, pois é uma condição altamente complexa de ser diagnosticada.…”
Section: Discussionunclassified
“…Under family features the following factors have been identified to help with recognition of the disorder: emotional neglect and psychological abandonment in childhood, not necessarily active abuse, although some authors have found a history of sexual abuse in the backgrounds of the perpetrator; unexplained and recurrent childhood illnesses which some of the literature sees relating to an earlier history of factitious or somatising disorders, an absent marital partner, marital discord, disturbed family relationships, unexplained Korpershoek and Flisher 6 illness or death of a sibling or another child in the perpetrator's care and familial pattern of illness presentation (Bools 1996, Feldman 1994, Folks 1995, Jureidini 1999, Leonard and Farrel 1992, Marcus et al 1995, Parnell and Day 1998, Polledri 1996, Schreier 1997, 2000, Sheridan 2003, Yorker and Kahan 1990.…”
Section: Family Featuresmentioning
confidence: 96%
“…(Bools 1996, Feldman 1994, Folks 1995, Jureidini 1999, Leonard and Farrel 1992, Marcus et al 1995, Parnell and Day 1998, Polledri 1996, Schreier 1997, 2000, Sheridan 2003, Yorker and Kahan 1990.…”
Section: Mother-perpetrator Featuresmentioning
confidence: 98%
“…Owing to mental status concerns, M other in order to meet his or her own emotional needs via the treatment process, is a poorly understood and controversial diagnosis. While many refer to it as a psychiatric disorder, described by DSM-IV 1 provisional research criteria as an extreme manifestation of factitious disorder by proxy (Table 1), 2,3 others argue strongly that it is more accurately described as medical abuse. 4,5 Proponents of the psychodynamic perspective describe victims as the object used to regulate the perpetrator's " .…”
mentioning
confidence: 99%